Strategi Experiential untuk Pembelajaran Penerapan Pola Lantai Tari Paduppa di Kelas VIII SMP Negeri 2 Bolano Lambunu Kabupaten Parigi Moutong - Zakaria, Masni (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research was motivated by problems found in the learning process which were caused by several factors, namely the one-way nature of the learning process, lack of student interest in learning, and lack of interaction between teachers and students. This research uses experiential learning strategies, this strategy can improve abilities and Students' interest in learning is through the experience they gain directly through 4 stages of implementation, namely concrete experience, observation and reflection, conceptualization, and experimentation. The results of research using this experiential strategy are able to build a varied and enjoyable learning atmosphere. So, of the 20 students sampled by the researchers, all of them usually danced the paduppa dance well